The Rise of Nonbanks and the Quality of Postorigination Mortgage Servicing - Degerli, Ahmet; Wang, Jing (The Review of Corporate Finance Studies, 2026)
Abstract As nonbanks’ market share increases in a local residential mortgage market, the quality of their postorigination mortgage servicing improves. This finding is confirmed by two instrumental variable analyses exploiting (1) stress tests conducted by the Federal Reserve, and (2) mortgage industry surety bonds required by each state. Evidence suggests that improvements in service quality arise through two channels. First, expansion in nonbank market share leads to greater lender specialization: nonbanks increasingly service lower-income borrowers, while traditional banks increasingly concentrate on higher-income segments. Second, higher nonbank market share is associated with increased investment in technology by nonbanks. (JEL G21, G23, L13, L15)Received: May 22, 2025